Revisiting the Contested Case of Belgrade Waterfront Transformation: From Unethical Urban Governance to Landscape Degradation - Corovic, Dragana; Korac, Srdan T; Milinkovic, Marija (Land (Basel), 2025)
This paper examines two large urban projects within a defined theoretical and methodological framework. Firstly, we analyse how the city administration in Belgrade, in post-socialist Serbia, managed the initial steps of the transformation of a part of the old town into the new large-scale development, the Belgrade Waterfront (BW), on the right bank of the Sava River. The contested outcome of the land transformation process contributes to a recognition of the unethical decision-making and performance of the responsible city authorities. Secondly, the postwar planning and construction of New Belgrade, in particular its Central Zone, is critically examined from the aspect of radical urban landscape transformation and its impact on society. Through a critical examination of the spatial development of the socialist period, we aim to identify emancipatory architectural and urban practises that could be an alternative to contemporary spatial production and that might provide a notion of key strategies for (re)establishing corresponding forms of socio-spatial justice. The two aforementioned research subjects are examined using different research questions, methodological tools, and different theoretical frameworks, which overlap, merge, and combine in the part of the study where the obtained results are discussed.